Promotion of methane storage in tetra-n-butylammonium sulfate semi-clathrate hydrate by inducing pure methane hydrate - Xu, Jie; Chen, Qinglin; Du, Jianwei (Chemical Engineering Journal, 2021)
Inducing pure methane hydrate from double methane semi-clathrate hydrate is a promising method to enhance methane storage in hydrate. In this work, comprehensive investigation on methane uptake contributed from induced methane hydrate was first conducted. A new halogen-free semi-clathrate hydrate former - tetra-n-butylammonium sulfate was chosen to form double semi-clathrate hydrate for methane storage. Classical isochoric method and thermal volumetric analysis along with pressure-temperature trace method were employed for this study. Experiments were carried out to measure methane uptake and phase equilibrium at wide mass fractions and pressures ranging from 17.0 to 50.0 wt% and 3.0 to 13.0 MPa, respectively. With induced methane hydrate, the maximum obtained methane uptake reached 127.6% of the theoretical methane capacity in double (TBA)(2)SO4 + CH4 semi-clathrate hydrate. Key parameters such as induction time, formation rate and dissociation enthalpy of this double methane + tetra-n-butylammonium sulfate semi-clathrate hydrate were also obtained. Formation rate curve with clear inflection can be divided into two parts corresponding to induced pure methane hydrate and double methane semi-clathrate hydrate distinctly. The conversion rate of free water into pure methane hydrate was first determined between 31.30% and 47.77% in this work. Accordingly, the mechanism of induced pure methane hydrate was proposed that the occupancy of methane in double methane semi-clathrate hydrate controls the extent of induced pure methane hydrate. The results in this study indicate tetra-n-butylammonium sulfate has the potential to deal with the challenge for methane storage in hydrate.